Differential analysis of sediment volume on fluid properties and debris flow disaster impact in the northwest traffic corridor of Sichuan Province - Ling LI; Ningsheng CHEN; Yi YANG; Zheng ZHONG; Na HUANG (Zhongguo dizhi zaihai yu fangzhi xuebao)
The LJ9 segment of Jiumian Expressway frequently experiences gully-type debris flow disasters, posing threats to nearby villages and infrastructure. Considering the unique characteristics and importance of the highway and G247 national road, this study investigates the material source characteristics and scale of six debris flow gullies with debris flow outbreak traces along the LJ9 section of Jiumian Expressway. The debris flows in this area are classified as low-frequency gully flash flood types. The bulk density of the debris flows ranges from 1.647 to 1.843 g/cm3, with velocities between 3.45 and 6.54 m/s, and flow rate ranging from 29.47 to 253.45 m3/s. The total volume of the debris flow ranges from 0.99×104 to 8.28×104 m3. This paper compares the differences in the scale characteristics of the “8•16” debris flow on the Jiumian Expressway, and analyze the relationship between the volume of material source and the bulk density and scale of debris flow, establishing relevant calculation formulas. The results show that: (1) The fluid properties of debris flow in the study area are classified as low-frequency gully flash flood types, closely related to the volume of material source, with a positive correlation between unit area material source volume and debris flow bulk density. When unit area material source volume exceeds 1.65×105 m3/km2 or falls below 1.13×105 m3/km2, debris flow exhibit viscous or diluted characteristics, respectively. (2) Under similar geological conditions, there is a linear correlation between material source volume and debris flow scale, with total debris flow volume decreasing as unit area material source volume decreases. (3) Debris flow damage potential is controlled by material source volume. Gullies with material source volumes exceeding 800 000 m3 are more likely to produce viscous debris flows, which has greater destructive power and form larger debris flow fans at their mouths. These findings provide insights for the design and construction of the Jiumian Expressway and serve as a scientific basis for the safe operation of infrastructure in mountainous regions and the construction work of geological hazard prevention projects.